UNVEILING THE INTERSECTION OF FINANCIAL SOCIALISATION AND ECONOMIC EQUITY AMONG TRIBAL WOMEN: A BIBLIOMETRIC ANALYSIS - Jena, Sanjeeb K; Badak, Kiri (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The present study performs a bibliometric analysis to investigate the connection between financial socialisation and economic equity among tribal women. The primary goal of this research is to evaluate the existing literature on this subject, offering an in-depth examination of the trends, research gaps, key authors, and critical concepts in this field. The study aims to provide a comprehensive overview that can inform and guide future research and support policymakers in prioritizing areas for further investigation to improve economic equity for tribal women. The analysis utilizes the Web of Science (WoS) database, ensuring the reliability of the data by including 777 peer-reviewed journal articles published between 2000 and 2024. To uncover meaningful patterns and insights, advanced analytical tools such as Bibliometrix (R package) Biblioshiny, and VOSviewer were employed. These tools helped identify key publication trends, leading sources, and key clusters related to financial socialisation and economic equity in the context of tribal women. This study provides valuable insights into an underrepresented area, shedding light on the complex intersection of financial behaviours and social inequalities. It outlines critical directions for future research, aiming to bridge the existing gaps and enhance the understanding of financial socialisation as a driver for economic equity among marginalised tribal communities.